HUBUNGAN STATUS GIZI DENGAN KEJADIAN DISMENOREA PADA REMAJA PUTERI DI SMP PGRI 01 KARANGPLOSO: HUBUNGAN STATUS GIZI DENGAN KEJADIAN DISMENOREA PADA REMAJA PUTERI DI SMP PGRI 01 KARANGPLOSO - rifzul maulina; Dewinta Ristawati; Rani Safitri (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: Adolescence is an important period in human life, often identified as puberty. At this stage, teenagers experience significant physical, emotional and social changes. One of the common problems experienced by teenage girls during puberty is dysmenorrhea or menstrual pain. Factors such as nutritional status have been identified as one of the factors that influence the incidence of dysmenorrhoea in adolescent girls. The aim of this research was to determine the relationship between nutritional status and the incidence of dysmenorrhea in young women at SMP PGRI 01 Karangploso. Methods: This research uses a quantitative approach with a cross-sectional design. The research population consisted of teenage female students who had experienced menstruation at SMP PGRI 01 Karangploso. The sampling technique used was total sampling. Data was collected through a questionnaire developed by researchers, and data analysis was carried out using univariate analysis and bivariate analysis methods, using the chi-square test. Results: The research results show that the majority of young women at SMP PGRI 01 Karangploso have normal nutritional status. However, more than half of them experience dysmenorrhoea. Statistical analysis shows that there is a significant relationship between nutritional status and the incidence of dysmenorrhoea in adolescent girls at the school. Conclusion: Penelitian ini menyimpulkan bahwa terdapat hubungan yang signifikan antara status gizi dengan kejadian dismenorea pada remaja putri di SMP PGRI 01 Karangploso. Temuan ini menyoroti pentingnya perhatian terhadap status gizi dalam kesehatan remaja putri.